Power transformer geometry monitoring of active parts by SFRA method - Ilić Denis; Milić Saša; Jovanović Đorđe (Zbornik Radova: Elektrotehnički Institut "Nikola Tesla", 2014)
During regular operation, power transformer windings are continuously exposed to electromechanical stresses and vibrations. Surges during lightning or short circuits may cause the weakening of the mechanical structure and the mechanical reinforcing parts of the core and windings. Any distortion of the projected geometry of the winding will reduce its ability to withstand subsequent overstressing, which can lead to a large deformation of the windings and major system faults. This paper presents an analysis of the frequency response of the transformer windings (Sweep Frequency Response Analysis - SFRA) as a method of determining the integrity of the core and winding geometry. The paper presents the results obtained experimentally and those from field tests on real transformers.